Sosisalisasi Penggunaan Beauveria Bassiana dan Pestisida Nabati untuk Mengendalikan Hama pada Sayuran Hidroponik - Lutfi Afifah; Nurcahyo Widyodaru Saputro; Ultach Enri (Institut Pertanian Bogor, 2022)
Vegetable cultivation using a hydroponic system in a green house is growing rapidly in the Ciampel area, Karawang Regency. One of the problems faced by hydroponic vegetable farmers is the attack of leaf-eating pests. The control of pests that attack vegetables has been using chemical pesticides which will pollute the environment and be harmful to human health. The purpose of this community service activity is to provide knowledge and skills in the use of biological agents for the fungus Beauveria bassiana and vegetable pesticides made from papaya leaf extract to control pests on hydroponic vegetables. This activity was carried out in September-November 2020 which was attended by the Women Farmers Group (KWT) in Mulyasari Village, Ciampel, Karawang. Activities are carried out in a structured and gradual manner starting from planning, site surveys, problem identification, technical guidance, mentoring, monitoring, and evaluation. Assistance to farmers has been carried out in approximately three months online and offline together with students from the Faculty of Agriculture, Singaperbangsa Karawang University. The results of the activity showed an increase in understanding about the dangers of using chemical pesticides on vegetables and the importance of pest control based on Biointensive Integrated Pest Management (IPM-Biointensive) using biological agents and botanical pesticides. In addition, the participants who took part in this activity were skilled at producing the biological agent Beauveria bassiana and vegetable pesticides with active papaya leaf juice. Farmers become more skilled at monitoring pests in the green house/field to monitor the presence or absence of pests in their crops. In addition, farmers have become more skilled in mass propagation of B. bassiana biological agents and vegetable pesticides. Mass propagation technique of B. bassiana uses alternative media, namely from feed corn.